2021
DOI: 10.1038/s41467-021-23026-x
|View full text |Cite
|
Sign up to set email alerts
|

bric à brac controls sex pheromone choice by male European corn borer moths

Abstract: The sex pheromone system of ~160,000 moth species acts as a powerful form of assortative mating whereby females attract conspecific males with a species-specific blend of volatile compounds. Understanding how female pheromone production and male preference coevolve to produce this diversity requires knowledge of the genes underlying change in both traits. In the European corn borer moth, pheromone blend variation is controlled by two alleles of an autosomal fatty-acyl reductase gene expressed in the female phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…Based on the typical roles of female moths as signal producers and male moths as signal receivers in the sex pheromone system, several evolutionary hypotheses, such as the stasis hypothesis, asymmetric tracking hypothesis, and wallflower hypothesis, have been proposed ( Allison and Cardé, 2016 ; Cardé and Baker, 1984 ; Groot et al., 2006 ; Roelofs et al., 2002 ); however there is no consensus. This is mainly because existing studies show that the synthesis of sex pheromones in females and the perception of sex information in males are regulated by different genes and under independent genetic control ( Gould et al., 2009 , 2010 ; Löfstedt et al., 1989 ; Dopman et al., 2004 ; Unbehend et al., 2021 ). Although the contributions of male and female traits to the evolution of sex pheromone communication remain controversial, it is undeniable that male moths' perception of sex pheromone is one of the key steps.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the typical roles of female moths as signal producers and male moths as signal receivers in the sex pheromone system, several evolutionary hypotheses, such as the stasis hypothesis, asymmetric tracking hypothesis, and wallflower hypothesis, have been proposed ( Allison and Cardé, 2016 ; Cardé and Baker, 1984 ; Groot et al., 2006 ; Roelofs et al., 2002 ); however there is no consensus. This is mainly because existing studies show that the synthesis of sex pheromones in females and the perception of sex information in males are regulated by different genes and under independent genetic control ( Gould et al., 2009 , 2010 ; Löfstedt et al., 1989 ; Dopman et al., 2004 ; Unbehend et al., 2021 ). Although the contributions of male and female traits to the evolution of sex pheromone communication remain controversial, it is undeniable that male moths' perception of sex pheromone is one of the key steps.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , linkage mapping studies have shown that regulatory alleles of the bab locus ( bab1/2 recent paralogs) explain natural variation in dimorphic pigmentation and ovariole number ( 23 , 26 , 40 ). In corn borer moths ( Ostrinia nubilalis ), male response to a polymorphic female pheromone blend is driven by a Z-linked regulatory variation in the first intron of bab ( 41 ). This same intron is within the Colias U -locus interval.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated likelihood ratio chi-square statistics for factors in the car package (Fox & Weisberg, 2019) and performed Tukey-corrected pairwise comparisons using emmeans (Lenth, 2019). To further analyze and visualize effects, we used several other R packages: dplyr (Wickham et al, 2018), ggplot2 (Wickham, 2016), MASS (Venables & Ripley, 2002), plyr (Wickham, 2011), survival (Therneau, 2020), and survminer (Kassambara et al, 2019). The standard error (SE) for the proportion producing eggs was calculated using the equation Havel et al, 2019).…”
Section: Me Thodsmentioning
confidence: 99%